The Effect of Progressive Tax, Number of Vehicles and Tax Arrears on Revenue Transfer of Motor Vehicle Title Fee in South Sumatra Province - Vialeta, Putri; Susetyo, Didik; Yulianita, Anna (Journal of Economic Development, Environment and People, 2020)
Abstract. The purpose of this study is to analyze the Effect of Progressive Taxes. Number of Vehicles and Tax Arrears on Revenue Transfer Fees for Motorized Vehicles at UPT Regional Revenue Agency of South Sumatra Province. In this writing the type of data used is panel data. The sample in this study was 16 District / City UPTs for 2017 - 2018. The analysis technique used was Ordinary Least Squared (OLS) using the Eviews 8. The estimation results of the regression equation showed that simultaneously progressive taxes, the number of vehicles and arrears had a positive effect and significant to the acceptance of Transfer of Motor Vehicle Title Fee, which can be seen from the probability value F of 0.000000 <0.05 (α = 5%).